(untitled) (Bangladesh Journal of Zoology, 2023)
A study was conducted on the diurnal activity patterns of chestnut-headed bee-eater (Merops leschenaulti) and green bee-eater (Merops orientalis) at Chittagong University Campus, Bangladesh in the year 2015. Six major activities (perching, flying, calling, feeding, diving, and preening) were recorded for both species during the study period. The two bee-eater species were observed to spend their maximum (M. leschenaulti: 37.63%; M. orientalis: 35.95%) time in perching, whereas the minimum time spent by M. leschenaulti was observed in diving (1.76%) and by M. orientalis was in feeding (2.17%). They were more active during 15:00 - 17:00 h (M. leschenaulti: 27.34%; M. orientalis: 27.23%) than other diurnal time blocks. Two species spent their highest (M. leschenaulti: 14.71%; M. orientalis: 14.00%) time performing different activities in June and the lowest (M. leschenaulti: 2.71%; M. orientalis: 3.46%) in January. Both bee-eaters were mostly (M. leschenaulti: 56.58%; M. orientalis: 53.07%) active in monsoon than in other seasons. The similar activity patterns between two bee-eater species could be influenced by similar lifestyles associated with their close taxonomic relationship. A number of ecological factors, such as temperature, humidity and precipitation could influence the daily, monthly and seasonal variations in activities. Bangladesh J. Zool. 51(2): 175-190, 2023